The Relationship between Knowledge and Faith in the Qur'an (Thematic Study in Tafsir Al Azhar) - Moh. Jufriyadi Sholeh; Muh. Rizqi Alfian Nur (Penerbit Hellow Pustaka, 2025)
Knowledge and faith are two main things from the aspect of human life, if knowledge and faith are separated it will have an impact on human daily actions, in this modern era there are many people who cannot maintain their faith, so that it spreads to their knowledge therefore the relationship between knowledge and faith will be the object of this research with the basis of the interpretation of Al-Azhar by Buya Hamka. The problem raised in this research is how the correct relationship between knowledge and faith according to Buya Hamka in his interpretation of the Al-Azhar interpretation and will be described in two fukos namely: 1. How is Hamka's interpretation of the verses of knowledge and faith in the Qur'an 2. How is the relationship between knowledge and faith in the Qur'an according to Buya Hamka, in this research the author uses a library research approach, for that later steps will be taken to identify, collect, process and review existing data related to the problem of the relationship between knowledge and faith, both in the form of primary data and secondary data accurately and factually. The final finding in this study is that strong faith is needed to face the tests in this modern era, where knowledge about religion is set aside and human faith is getting weaker in today's era and according to Buya Hamka faith must be accompanied by knowledge, seen in the Tafsir al-Azhar the relationship between knowledge and faith brings an important value for human life in building harmony with both God and the social environment.